Stability and Removal of Naproxen and Its Metabolite by Advanced Membrane Wastewater Treatment Plant and Micelle-Clay Complex - Qurie, Mohannad (2014)
Naproxen, a non-steroidal anti-inflammatory drug, commonly used for fever, inflammation and for different health problems, as found for many pharmaceuticals has been recently detected in sewage effluents, surface, and ground water, and sometimes even in drinking water. An advanced wastewater treatment plant (WWTP), utilizing ultra-filtration, activated charcoal (AC), and reverse osmosis (RO) after the primary biological treatment, showed that both nano- and micro-ultrafiltration were not sufficient for removing spiked naproxen to a safe level, whereas RO membrane was quite efficient. No naproxen degradation was detected in pure water whereas it underwent biodegradation within three days in activated sludge giving O-desmethyl-naproxen. Adsorption performed on micelle-clay complex and AC under steady state conditions, showed that the former adsorbent is highly effective in removing naproxen with fast kinetics. Laboratory micelle-clay complex filters under continuous naproxen-spiked water flowing were found to be efficient in removing this drug, suggesting that the efficiency of existing advanced WWTP could be improved by including filtration columns filled with suitable sand/micelle-clay mixtures.